PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI: STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Rahmawati, Alni; Aini, Afifah Nur (Bussman Journal : Indonesian Journal of Business and Management, 2026)
This study aims to analyze and test the influence of corporate social responsibility and good corporate governance on firm value, with financial performance as a mediating variable, in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This study uses a quantitative approach using secondary data. The sample size was 114 from 46 companies, obtained using a purposive sampling method. The analytical tools used were Stepwise Linear Regression and Path Analysis with E-Views 12 software. The results of this study indicate that corporate social responsibility has no significant effect on firm value, good corporate governance has no significant effect on firm value, financial performance has a significant positive effect on firm value, corporate social responsibility has no effect on financial performance, good corporate governance has no effect on financial performance, financial performance is unable to mediate the effect of corporate social responsibility on firm value, and financial performance is unable to mediate the effect of good corporate governance on firm value